Try the Free Math Solver or Scroll down to Resources!

 Depdendent Variable

 Number of equations to solve: 23456789
 Equ. #1:
 Equ. #2:

 Equ. #3:

 Equ. #4:

 Equ. #5:

 Equ. #6:

 Equ. #7:

 Equ. #8:

 Equ. #9:

 Solve for:

 Dependent Variable

 Number of inequalities to solve: 23456789
 Ineq. #1:
 Ineq. #2:

 Ineq. #3:

 Ineq. #4:

 Ineq. #5:

 Ineq. #6:

 Ineq. #7:

 Ineq. #8:

 Ineq. #9:

 Solve for:

 Please use this form if you would like to have this math solver on your website, free of charge. Name: Email: Your Website: Msg:

Definition. A quadratic equation in x is an equation that can be written in the form
ax2 + bx + c = 0, where a ≠ 0.

Examples: x2 + x = 2, x2 + 6x + 5 = 0.
Zero Factor Theorem. If p and q are algebraic expressions, then

pq = 0 if and only if p = 0 or q = 0.

Example 3.1. Solving an equation by factoring.
Solve the equation x2 + x = 2.

Note: To use the method of factoring, it is essential that only the number 0 appear on one
side of the equation.
x2 + x = 2 subtract 2
x2 + x - 2 = 0 factor
(x - 1)(x + 2) = 0 zero factor theorem
x - 1 = 0 or x + 2 = 0
x = 1 or x = -2
So the solutions to the given equation are 1 and -2.

Example 3.2. Solving an equation by completing the square.
Solve the equation x2 + 6x + 5 = 0.

It is convenient to write the equation such that only terms involving x are on the right.
Thus we have

x2 + 6x = -5.

We are trying to find a square of the type (x + a)2 such that when expanded it contains
the terms x2, 6x and a number. In this case, the square is (x + 3)2, which expands as
x2 + 6x + 9. So to complete the square we add 9 both sides and we obtain the following
equivalent equations: Quadratic Formula . If a ≠ 0, then the roots of ax2 + bx + c = 0 are given by Note: If the discriminant b2 - 4ac is negative, the equation does not have real roots, but
we will learn in the next section that if r is a positive number then we can use complex
numbers to define the principal square root of -r by , where i is a special
complex number with the property that i2 = -1.

Example 3.3. Solving an equation using the quadratic formula.
Solve the equation 2x2 - 6x + 3 = 0.
We have a = 2, b = -6, c = 3. Thus 